Prevalence and risk factors for musculoskeletal disorders in dentists - Vuletić Jelena; Potran Michal; Kalem Dijana; Panić Zorica; Puškar Tatjana (Serbian Medical Society - Dental Section, Belgrade, 2013)
Introduction. Working in dental practice requires clear working field and easy access to all parts of oral cavity. For this reason, dentists often take non-physiological positions during treatment increasing the risk for musculoskeletal disorders. The aim of this study was to determine the prevalence of musculoskeletal disorders in dentists with different work experience in Novi Sad. Material and Methods. The study included 89 dentists. Data related to musculoskeletal disorders was collected using a questionnaire. Potential risk factors for musculoskeletal disorders were detected and analyzed. Results. Out of 89 dentists, 32 (36%) were male and 57 (64%) were female. Musculoskeletal disorders were detected in 62 dentists (69.7%). 50% of dentists reported pain during first three years of work in the office, while others noted these problems later. 49 dentists (77.8%) reported increasing pain during the day. Of the total respondents, 76.2% had pain in neck, 71.4% reported discomfort in the upper part of their back, 68.3% in the region of shoulder, and 65.1% complained for pain in lower back. Lower prevalence of pain was found in the region of wrists and hands, hips, knees, ankles and elbows. Statistical analysis did not show significant difference between observed risk factors. Conclusion. The prevalence of musculoskeletal disorders in examined dentists in Novi Sad was 69.7%. It was higher in male compared to female respondents. Most dentists had musculoskeletal disturbances in the region of neck, shoulders and upper back.